A cross-country perspective on solar energy in urban planning: Lessons learned from international case studies. (July 2019) - Lobaccaro, G.; Croce, S.; Lindkvist, C.; Munari Probst, M.C.; Scognamiglio, A.; Dahlberg, J.; Lundgren, M.; Wall, M.
Abstract: This work, framed in the IEA SHC Task 51 "Solar Energy in Urban Planning", presents an illustrative perspective of solar energy in urban planning through the analysis of 34 international case studies conducted in 10 countries. The aim here is to examine challenges, barriers and opportunities for active solar systems and passive solar strategies by taking into consideration interrelated technical and non-technical aspects in ongoing and completed projects. It focuses on exposing potential pitfalls and illustrating lessons learned in case studies divided into three categories: (i) existing urban areas, (ii) new urban areas, and (iii) solar landscapes. The analysis has yielded insights into the solar energy strategy adoption, the evaluation of solar energy production, solar irradiation and daylighting, and the architectural quality, sensitivity and visibility of the solar systems for urban planning. The outcomes have implications to stimulate successful practices in implementing solar strategies in urban planning and facilitating their replicability worldwide by avoiding common mistakes. Highlights: International case studies' collection in existing, new urban areas and landscapes. Illustrative perspective of lessons learned on solar energy in urban planning. Identification of challenges, barriers and opportunities for solar implementation. Approaches, methods and tools to develop energy concept and solar integration. Evaluation of architectural visibility, sensitivity and quality of solar systems.